PERBANDINGAN REGULASI ZAKAT DAN PENYELEWENGAN ZAKAT DI INDONESIA DAN MALAYSIA - Hallasurra Alisain Chandrakirana; Ida Musofiana; Achmad Sulchan (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This research aims to analyze zakat regulations in Malaysia and Indonesia with a focus on comparing key aspects in the management and enforcement of zakat laws. The research method used is a qualitative method with library study data collection techniques. The main objective of this research is to understand the differences and similarities in the structure of zakat management, the sanctions and penalties imposed for zakat misappropriation, as well as the effectiveness of zakat law enforcement in the two countries. The research results show that Malaysia has a more centralized approach in managing zakat with the Department of Zakat and Hajj (JAWHAR) acting as a central government agency. On the other hand, Indonesia adopts a more decentralized approach involving various national, provincial and local zakat bodies, as well as zakat amil institutions operating at the village or sub-district level. The differences in zakat management structures reflect differences in the approaches to zakat regulation in the two countries. In addition, Malaysia imposes a fine of up to 1,000 ringgit and/or a prison sentence of up to six months for zakat violations, while Indonesia imposes a prison sentence of up to 5 years and/or a maximum fine of IDR 500,000,000.00. Even though both have laws regulating zakat, the effectiveness of zakat law enforcement is still a challenge in both countries. To improve zakat regulations, Malaysia and Indonesia have made improvements, including increasing public understanding of zakat, increasing transparency in zakat management, and strengthening zakat supervision and law enforcement bodies. With these various initiatives, it is hoped that zakat regulations in both countries can become more effective in maintaining the integrity of the zakat system and supporting the welfare of the wider community.